2014
DOI: 10.1007/s00787-014-0644-6
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive bias and unusual experiences in childhood

Abstract: Cognitive therapy is recommended for children with psychotic-like, or unusual, experiences associated with distress or impairment (UEDs; UK National Institute for Health and Care Excellence, 2013 [1]). Accurate models of the psychological underpinnings of childhood UEDs are required to effectively target therapies. Cognitive biases, such as the jumping to conclusions data-gathering bias (JTC), are implicated in the development and maintenance of psychosis in adults. In this study, we aimed to establish the sui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 49 publications
2
16
0
Order By: Relevance
“…In recent studies, the psychosocial factors implicated in the onset, severity, and maintenance of adult psychosis have been found to also predict the occurrence and severity of childhood UEs [28][29][30][31][32][33][34]. Our research has shown that cognitive, emotional and social factors each make independent contributions to overall UE severity, supporting the general applicability of CBTp to this group [30].…”
Section: Introductionsupporting
confidence: 78%
See 4 more Smart Citations
“…In recent studies, the psychosocial factors implicated in the onset, severity, and maintenance of adult psychosis have been found to also predict the occurrence and severity of childhood UEs [28][29][30][31][32][33][34]. Our research has shown that cognitive, emotional and social factors each make independent contributions to overall UE severity, supporting the general applicability of CBTp to this group [30].…”
Section: Introductionsupporting
confidence: 78%
“…Our research has shown that cognitive, emotional and social factors each make independent contributions to overall UE severity, supporting the general applicability of CBTp to this group [30]. We have also shown that reasoning [31] and negative schematic beliefs [32] can both be assessed in children in a similar fashion to adults with psychosis, and could both form useful foci for intervention. However, it remains unclear whether childhood UEs share characteristics of dimension, and content or type, with adult symptoms of psychosis, and, if so, whether there is similar variation in associated psychosocial processes to support the development of targeted interventions.…”
supporting
confidence: 72%
See 3 more Smart Citations